THE DIRECTING ANIMATION FILM ENTITLED SI JOE - Satria Veriansyah Wiguna; Ranang Agung Sugihartono (Institut Seni Indonesia Surakarta, 2020)
The re-introduction of the Nusantara folklore is very important because it is a form of the original culture of the archipelago and a national identity. An animated film work that tells the story of a parody about Timun Mas folklore is expected to be able to reintroduce a folklore from Central Java by adding novelty to the portrayal of the characters and stories. The making of this work aims to create a 2.5D animated film with the theme of folklore with new packaging. The artistic creation doing by the director is to combine and move 2D animation in a 3D space perspective, so that 2.5D animation is created. 2.5D animation was created using a virtual camera so that it produces better image movement than an ordinary 2D animation. This animation work that explores the folklore of the archipelago shows success in aspects of the uniqueness and impression in the visualization and novelty of the story. This animated film can bring back the old story so it is enjoyable to watch by millennial audiences.